ASSESSMENT OF UNIVERSAL NEONATAL HEARING SCREENING: OUTCOMES AND PREVALENCE AT A TERTIARY CARE CENTER - DESAI, TRIVENI; KAMATH, RASHMI; MANTHALE, AISHWARAYA; SHIRSHETTY, ARUN KUMAR (International Journal of Current Pharmaceutical Research, 2025)
Objective: Early detection of hearing impairment through Universal Neonatal Hearing Screening (UNHS) is crucial for timely intervention. This study assesses the outcomes and prevalence of hearing loss in neonates screened at a tertiary care center. Methods: This prospective observational study involved 1175 neonates born at SDM Medical College and Hospital between December 2019 and November 2020. Neonates underwent initial and, if necessary, repeat hearing screenings using the Otoacoustic Emission (OAE) technique. Data on gender and birth weight distribution were also analyzed to explore demographic correlations with screening outcomes. Results: Of the neonates screened, 99.40% passed the initial hearing test, while 0.60% were referred for further evaluation. Among those referred, 71.43% passed on repeat screening, with 28.57% continuing to show potential hearing issues. The majority of neonates weighed over 2.5 kg, indicating a lower presence of very low birth weight infants in the screened population. Conclusion: The high pass rate in initial screenings demonstrates the effectiveness of the OAE method in a tertiary care setting, though the importance of follow-up testing for those referred remains critical. The study highlights the successful implementation of UNHS and underscores the need for continuous monitoring and adaptation of screening protocols to address all potential risks in neonatal hearing loss.